Antiprotozoal Drugs - Thurston, Scott (Side Effects of Drugs Annual, 2015)
The Side Effects of Drugs Annuals is a series of volumes in which the adverse effects of drugs and adverse reactions to them are surveyed. The series supplements the contents of Meyler's Side Effects of Drugs: the International Encyclopedia of Adverse Drug Reactions and Interactions. This review of the July 2013 to December 2014 publications on antiprotozoal drugs covers various antimalarial drugs (4-aminoquinolines chloroquine and hydroxychloroquine, mefloquine, pyrimethamine, proguanil hydrochloride and atovaquone, quinine, artesunate, the combination of artesunate + pyronaridine, metronidazole and ornidazole). This review describes changes in the pharmacokinetics of antimalarial drugs, particularly first-line regimens of artemisinin-based compounds, lumefantrine, chloroquine and pyrimethamine + sulphadoxine that occur in pregnancy.